Pengaruh Tingkat Kepatuhan Wajib Pajak Badan Terhadap Peningkatan Penerimaan Pajak Penghasilan Dengan Penagihan Pajak Sebagai Variabel Moderating (Pada KPP Pratama Cilandak Jakarta Selatan) - Diera Darmayani; Eva Herianti (Universitas Trunojoyo Madura, 2017)
This study examined the influence of the level of institution of the tax compliance to increase of the tax revenue with tax collection as moderating variable. The population in this study were of the intitutions the tax that listened in the Tax Jakarta Cilandak. Samples in this study are taken from 2012- 2014. The method of determining the sample was judgement sampling method, while the data processing methods used by researcher was multiple linear regresion analysis. The result shows that the level of institutian of the tax compliance significantly influence the increase of the tax revenue because the statistical t-test results showed that tcount ttabel(2,441 2,028) and the significant value show that the probability less than 0,05. Variable does not affect the ability of tax collection is in the disbursement of increase of the tax revenue, because the statistical t-test results showed that tcount ttabel (-1,026 2,028) and the significant value show that the probability smaller from 0,05.Tax collection can not be a moderating variable for level of institution of the tax compliance